URGENCY AND TECHNIQUES FOR USING THE QUIZIZZ APPLICATION IN LEARNING OF ISLAMIC EDUCATION LESSONS - Miswar Miswar (Journal of Learning on History and Social Sciences, 2024)
The development of learning technology is a development in independent learning in the digital era. It can even be said that the role of learning technology development of Islamic Education Lessons is related to the use of information and communication technology in this digital era is very high. The development of learning technology is an actor in e-learning in the learning process. The development of learning technology is one of the parties that plays a significant role in learning , and is a catalyst for learning in the digital era. Learning in the digital era cannot be separated from the use of technology or what is commonly called e-learning. Especially with the goal of independent learning, namely preparing students to face socio-cultural changes and technological developments. One way is to use the Quizizz application. Learning of Islamic Education Lessons with Quizizz is here to help teachers and students so that the learning process can take place and enjoyable learning experiences can be experienced when distance learning is carried out. Q uizizz is a student engagement platform that allows teachers to conduct interactive lessons and quizzes with their students. Created interactive quizzes have up to 5 answer choices including the correct answer and can add an image to the background of the question. Quizizz can provide data and statistics about student performance results in real time. Quizizz can not only be done while studying in class, but can also be made up of questions for homework, so students can play it anytime and anywhere as long as it does not exceed the allotted time limit. This of course makes it easier for teachers to give assignments such as exercises or tests to students while continuing to supervise online and avoiding students who cheat in learning of Islamic Education Lessons.